Immunohistochemical study of the brain aquaporin-4 in the rat acute liver failure model - Shulyatnikova, T. V.; Tumanskiy, V. O.; Шулятнікова, Тетяна Володимирівна; Туманський, Валерій Олексійович (My University, 2022)
Abstract. Acute liver failure as well as acute-on-chronic liver failure result in the development of acute hepatic encephalopathy (HE) characterized by the major pathophysiologic event in form of the brain edema formation. Among brain cells, astrocytes are considered to be a central cellular population most sensitive to ammonia exposure in HE being the primarily cellular source of glutamine synthetase for ammonia metabolism. Astrocyte swelling is considered to be a principal sign of acute HE, while the exact molecular mechanisms of this event are still not fully understood. According to current concepts on HE, alteration in AQP4 regulation can play one of the central roles in the brain edema development and progression in hyperammonemia states. Considering high region- and context-specific heterogeneity of astroglial populations in the CNS, AQP4 involvement in the links of HE can also sustain mentioned conventional diversity. The aim of the study: to determine the immunohistochemical level of the brain aquaporin 4 (AQP4) expression in the experimental acute liver failure in rats. Резюме. Астроцитарний набряк вважається ключовою ознакою гострої печінкової енцефалопатії, проте точні молекулярні механізми цього явища вимагають подальшого вивчення. Мета. Імуногістохімічне визначення рівня експресії мозкового аквапорину-4 (AQP4) при експериментальній гострій печінковій недостатності у щурів. Матеріали та методи. Дослідження проведено на щурах лінії Вістар: 5 контрольних тварин та 10 щурів з моделлю гострої печінкової недостатності (ГПН), індукованої ацетамінофеном (AILF). Імуногістохімічне дослідження експресії AQP4 проводили у сенсомоторній корі, підкірковій білій речовині, гіпокампі, таламусі та хвостатому ядрі/скорлупі в період між 12 і 24 год після ін'єкції ацетамінофену.
Імуногістохімічне дослідження мозкового аквапорину-4 у моделі гострої печінкової недостатності у щурів
Shulyatnikova T. V. - ORCID ID: 0000-0002-0196-9935; Tumanskiy V. O. - ORCID ID: 0000-0001-8267-2350.
Keywords: acute hepatic encephalopathy; astroglial reactivity; AQP4; гостра печінкова енцефалопатія; астрогліальна реактивність